Peran Moderasi Dalam Membangun Toleransi Beragama - Khairunisa; Shela Rahmayanti (4, 2024)
The pluralistic Indonesian nation consists of many different cultures. Diversity in terms of language, race, religion, ethnicity, customs, and culture. Adhering to one's own views is not religious tolerance. In addition, avoid exchanging views with other religious communities. The development of religious tolerance is greatly assisted by this discussion. This study uses a qualitative research methodology, collecting data from various publications that have been studied by other researchers. Therefore, the next stage is to conduct additional analysis and rearrange the data according to the system that the author has created. The purpose of this study is to clarify how moderation contributes to the development of tolerance for rules. In order for both parties to respect and appreciate each other's talents and shortcomings, they must be able to supervise each other and build an environment full of tolerance. This is the essence of moderation within the framework of tolerance. Abstrak Bangsa Indonesia yang majemuk terdiri dari banyak kebudayaan yang berbeda-beda. Keberagaman baik dari segi bahasa, ras, agama, suku, adat istiadat, dan budaya. Mematuhi pandangan sendiri bukanlah toleransi beragama. Selain itu, hindari bertukar pandangan dengan komunitas agama lain. Perkembangan toleransi beragama sangat terbantu oleh perbincangan ini. Penelitian ini menggunakan metodologi penelitian kualitatif, mengumpulkan data dari berbagai publikasi yang telah diteliti oleh peneliti lain. Oleh karena itu, tahap selanjutnya adalah melakukan analisis tambahan dan menata ulang data sesuai dengan sistem yang telah penulis buat. Tujuan dari penelitian ini adalah untuk memperjelas bagaimana moderasi berkontribusi terhadap pengembangan toleransi terhadap aturan. Agar kedua belah pihak dapat saling menghormati dan menghargai bakat dan kekurangan masing-masing, maka harus mampu saling mengawasi dan membangun lingkungan yang penuh toleransi. Inilah inti dari moderasi dalam kerangka toleransi.